Cutaneous denervation in Progressive Supranuclear Palsy. Issue 1 (January 2019) - Nolano, M.; Provitera, V; Caporaso, G; Manganelli, F.; Stancanelli, A.; De Michele, G.; Santoro, L.
Abstract : Progressive Supranuclear Palsy (PSP) is a rare neurodegenerative disease characterized by intraneuronal accumulation of hyperphosphorylated Tau. Because PSP is strongly linked biochemically and genetically to tau protein abnormalities there is a growing interest in new tau-directed therapies and in the search of new biomarkers able to monitor disease progression. We studied cutaneous innervation in PSP in order to identify new biomarkers of nerve degeneration trough a minimally invasive technique such as skin biopsy. We performed 3 mm punch biopsies from thigh, leg and fingertip of 12 PSP patients (mean age = 68.4 ± 7.8). Samples were processed with indirect immunofluorescence using a large panel of antibodies to visualize and quantify sensory and autonomic cutaneous nerves. Results were compared with those obtained from a population of age and sex matched controls (mean age = 69 ± 3.3). In PSP patients, compared to controls, we found a severe length-dependent loss of intraepidermal nerve fibers associated to a severe loss of autonomic vasomotor, sudomotor and pilomotor nerves. Moreover, we observed a marked loss of Meissner corpuscles and intrapapillar myelinated endings in glabrous skin. The pattern of nerve degeneration appeared different compared to other neurodegenerative disorders. Skin may provide useful neuropathogical biomarkers to study PSP progression.